Sexual Behavior in the Human Male. by Alfred C. Kinsey, Wardell B. Pomeroy, and Clyde E. Martin. (Philadelphia and London, W.B. Saunders Co. 1948) (1948)
Title page (no illus.).
Illus. in: Sexual Behavior in the Human Male. by Alfred C. Kinsey, Wardell B. Pomeroy, and Clyde E. Martin. (Philadelphia and London, W.B. Saunders Co. 1948).
Reference copy may be in LOT 4394.
This record contains unverified, old data from caption card.
Caption card tracings: PI--WORKS; Manners & customs; Shelf.